GOODS CLASSIFICATION USING ABC AND VESO METHODS - Fauzi, Muchammad (International Journal of Psychosocial Rehabilitation, 2020)
UStore needs to know what product items have the highest and lowest contribution to the value of money generated, so that UStore can develop strategies to increase sales. Therefore UStore needs to manage all inventory items. The purpose of this study is to find out which items have the highest to lowest contribution to sales in 2018 so that UStore can find out which types of items are a priority to be managed by the suppliers. The research method uses a quantitative approach to classify the level of importance, namely the ABC method that classifies inventory based on its value and the level of technical importance of VESO (Vital, Essential, Support, Operating). Of the 11 (eleven) product categories in UStore, the product items that have the highest contribution are Lanyards, because they are categorized as A and Vital.